Is allogeneic transplantation really the best treatment for FLT3/ITD‐positive acute myeloid leukemia? A systematic review. (2nd January 2015) - Ma, Yingying; Wu, Yazhou; Shen, Zhaohua; Zhang, Xi; Zeng, Dongfeng; Kong, Peiyan
Abstract Fetal liver tyrosine kinase 3 (FLT3)–internal tandem duplications (ITDs) has been used as a powerful adverse prognostic indicator for acute myeloid leukemia (AML) in any age group. Evidence is mixed regarding the effects of allogeneic transplantation (allo‐HSCT) in first complete remission (CR) for patients with FLT3/ITD AML. To fill this gap, this study provides a systematic review and meta‐analysis of patients with FLT3/ITD AML receiving HSCT. A search of PubMed, Embase, and OVID yielded 1706 abstracts, two researchers screening the trials based on inclusion and exclusion criteria, and assessed the methodology quality independently. Meta‐analysis showed that compared with chemotherapy, both allo‐HSCT and autologous hematopoietic cell transplantation (auto‐HSCT) can reduce the relapse rate (p < 0.01) and improve both the OS (p < 0.01) and DFS (p < 0.01). But when compared allo‐HSCT with auto‐HSCT, the OS (p = 0.27) and DFS (p = 0.19) have no statistical significance, and only the relapse indicator has statistical significance, p < 0.01. Based on the results, we can conclude that allo‐HSCT is an efficient therapy approach for patients with FLT3/ITD AML. Chemotherapy cannot change the poor prognosis. Auto‐HSCT can improve OS and DFS, but it cannot reduce the relapse rate.